The dilemma of management of cystic lesions; an uncertain way forward: a case report - Umer, Fahad; Adnan, Niha; Khan, Madiha; Qureshi, Madiha Bilal (Journal of the Pakistan Medical Association, 2023)
Periapical diseases ranges from mild granulomatous lesions to large cystic ones, with the treatments corresponding to their respective pre-operative diagnoses. However, the determination of cause of periapical radiolucency is impossible on pre-operative clinical and radiographic examinations. We present a case highlighting the difficulties encountered in treating a periapical cyst using the current evidence in literature. It demonstrates the uncertainty involved in treating such lesions, owing to the impossible nature of determining the histopathological nature of the cyst, i.e., being either true cysts or pocket cysts. This case includes orthograde re-treatment; decompression of the cystic lesion, followed by peri-apical surgery of two teeth over a course of three years; and the uncertain outcomes encountered after each phase of the treatment. Keywords: Granuloma, periradicular lesion, apical cyst, periapical surgery, non-surgical retreatment.